INTEGRATIVE COMMUNICATION IN CONSERVING TAOISM AND CHINESE CULTURE SIU HOK BIO TEMPLE SEMARANG, CENTRAL JAVA - Nurtyasih Wibawanti Ratna Amina; Suwandi Sumartias; Siti Jamilah Az Zahra; Sherica Rafa Almira (Universitas Padjadjaran, 2023)
Pagoda as a cultural product and religious institution that must be maintained as a national cultural treasure. Siu Hok Bio Temple is one of the oldest temples in Semarang. The pagoda is able to maintain the authenticity of the building and the values of Chinese culture and Taoist religious values, and even become a center of reference for the culture and values of Taoism. However, there are concerns about its sustainability because there is no younger generation who want to continue their cultural and religious values. Starting from this, this research wants to examine by focusing on the efforts of pagodas to maintain their existence as centers of Chinese culture and Taoist values in areas where the majority are of other religions. This research uses a theoretical approach through the perspective of social exchange evolution theory developed by Sillar, 2019 and ICT (Integrative Communication Theory) theory, 2005. The research method uses subjective interpretive research, a qualitative approach through participatory research. The conclusion of the research shows that the external approach to the environment is carried out in participatory communication quite successfully. However, in building communication with the congregation the pagoda tends to be puritanical and conservative, so that integrative communication cannot be carried out, which in the end does not occur conducive social exchange. The recommendation is to separate the values of Taoism and Chinese culture in order to be adaptive to the younger generation who have entered the digital world.